Home literacy environment of preschool children: a scoping review - Wee, Phei Phei; Abdullah, Nur A; Mohamed Zain, Nor Azrita; Jusoh, Masnira; Zakaria, Mohd N (Nova Science Publishers, Inc., 2023)
The purpose of this review was to explore the key instrumentations and dimensions of the home literacy environment of typically developing preschool children and those with disabilities. Search of articles was conducted in five databases. Snowballing technique was used to search articles from the reference list of previous systematic review and metaanalysis studies. From 1,913 articles, a total of 13 articles were retained. Data were charted according to the parents’ and children’s characteristics and five main dimensions of HLE, namely: literacy resources, formal literacy (i.e., reading and writing activities), informal literacy (i.e., shared reading behavior, frequency of shared reading, time of shared reading), parental beliefs and attitude, and children’s interests. Mixed findings in literacy resources, informal and formal literacy, and children’s interests were reported. However, most parents in the studies believed that early education started at home, and they played important roles in facilitating their children’s language and literacy development. The lack of a single, universally used instrument inhibited the ability to synchronize the assessment and outcomes of the home literacy environment across preschool children from different cultural backgrounds and countries.